Plačilo storitev z osebnimi podatki? - Renko, Jernej (Podjetje in delo, 2021)
The most important novelty that the adoption of Directive (EU) 2019/770 brings to the European legal area is the regulation of contracts in which the consumer provides their personal data to the trader in exchange for the supply of digital content and services. Given the implications of the new regulation on data protection law, the author first defines the relationship between Directive (EU) 2019/770 and Regulation (EU) 2016/679, and then analyses the conditions regarding characteristics of consumer's (personal) data and modalities of their provision to the trader, which must be met in order for this data to qualify as a contractual performance. The core of consumer's obligations in such contracts is not personal data itself, but the consent to the processing thereof under Regulation (EU) 2016/679. The author further discusses the interaction between consumer contract law and data protection law, and the consequences of consumer's withdrawal of their consent to the processing of personal data (as a fundamentally non-disposable right of the individual) for the contract concluded under Directive (EU) 2019/770.
Keywords: consent to the processing of personal data; consumer contract law; consumer sales; DCSD; Directive (EU) 2019/770 on the supply of digital content and digital services; Direktiva (EU) 2019/770 o dobavi digitalnih vsebin in digitalnih storitev; GDPR; personal data protection; plačilo z osebnimi podatki; potrošniška prodaja; potrošniško pogodbeno pravo; privolitev v obdelavo osebnih podatkov; varstvo osebnih podatkov